Control of the dispersed-to-continuous transition in polymer blends by viscoelastic asymmetry. (3rd January 2018) - You, Wei; Yu, Wei
Abstract: Controlling the dispersed-to-continuous transition (DCT) in immiscible polymer blends is still a challenging task due to multiple parameters dependency of DCT in the mixing process. In this study, the DCT of different polymer blends was investigated through controlling the viscoelastic asymmetry of polymers. The results demonstrate that the DCT is well correlated with the deformation of the dispersed domains and the ability to raise the aspect ratio of the dispersed domains. Both the viscosity ratio and the elasticity ratio are important to determine the aspect ratio of the dispersed domains. A diagram was suggested to control the DCT concentration by viscoelastic asymmetry, i.e., viscosity ratio and elasticity ratio. It is proved that DCT concentration as low as about 10% can be achieved for Polycarbonate/Poly (lactic acid) (PC/PLA) blends at the suitable viscoelastic asymmetry. Graphical abstract: Image 1 Highlights: The key to control the DCT is the ability to tune the aspect ratio of the dispersed domains. Both the viscosity ratio and the elasticity ratio are beneficial to keep the aspect ratio of the dispersed domains. A diagram was suggested to control the DCT concentration by viscoelastic asymmetry.